Theoretical Study of The Electromagnetic Structure of Boron Isotopes Using Local Scale Transformation Technique - Mohammed, Saja H.; Ridha, Arkan R. (Iraqi Journal of Science, 2018)
The radial wavefunctions of transformed harmonic-oscillator in the local scale transformation technique are used to calculate the root-mean square proton, charge, neutron and matter radii, nuclear density distributions and elastic electron scattering charge form factors of stable (10,11B) and (unstable) exotic (8,14,17B) Boron isotopes. For 10B and 11B, the transformed harmonic-oscillator wavefunctions are applied to all subshells in no-core shell model approach using wbp interaction. For 8,14,17B, the radial wavefunctions of harmonic-oscillator and THO are used to calculate the aforementioned quantities for the core and halo parts, respectively. The calculated matter and charge density distributions are found to be in very good agreement with experimental data for 8,14,17B and 10,11B, respectively. The calculated elastic electron scattering form factors of the longitudinal C0+C2 components for 10,11B are in very good agreement with experimental data.